Potensi Pengembangan Ekonomi Hijau Di Kabupaten Pangkajene Dan Kepulauan - Hardianti, Hardianti; Kartini, Yuni; swandani, swandani; Waworuntu, Ahmad Yusdarwin (Movere Journal, 2025)
This research aims to identify the potential for green economic development in Pangkajene and Islands Regency. The research method uses qualitative analysis. This research design was carried out by collecting primary and secondary data, data collection methods collected through various data sources in Pangkajene and Kepuluan Districts and in-depth interviews with several informants from the local community and stakeholders. Based on research results, Pangkajene and Islands Regency has significant green economic potential including marine tourism (ecotourism, beach and island tourism), sustainable fisheries (fish, shrimp, lobster), and organic farming (vegetables, fruit, medicinal plants) . Green economic development can improve community welfare and preserve the environment, such as increasing community income, creating employment opportunities, developing local industry, increasing contribution to district GDP, and reducing dependence on traditional sectors. Effective policies and strategies are needed to develop a green economy by developing green infrastructure, increasing public awareness, developing environmentally friendly technology, developing cooperation with related institutions, and developing green economic policies.